Korelasi Diameter Testis dan Berat Testis Terhadap Berat Badan Kucing Domestik (Felis catus) - Sari, Dian Ayu Kartika; Apritya, Desty; Rahman, Mohammad Noor (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
This research aimed to identify if there is a relationship between testicular diameter and testicular weight on the body weight of domestic cats (Felis catus). The samples used were 30 pairs of local/domestic cat testicles. Cats are fasted for 6-12 hours. Then the anaesthetic injection of Atropine was given at a dose of 0.02 mg/kgBW, Acepromazine at a dose of 0.2 mg/kgBW, Ketamine at a dose of 15 mg/kgBW. The testicles obtained from the castration process are weighed with a digital scale. Then measure the diameter using a digital calliper at the largest diameter horizontally. The parameters identified in this study were cat body weight, testicular weight and testicular diameter. The data obtained indicates a weak correlation between body weight and both testicular weight and testicular diameter.